Foreign Body Granuloma in the Maxillofacial Region: Report of an Unusual Case - Orozco-Gallardo, Mónica; Gutiérrez-Cortés, Evangelina; Vázquez-Alcaraz, Silverio Jafet; Valdivia, Andréa Dolores Correia Miranda (Odovtos - International Journal of Dental Sciences, 2022)
This paper aimed to present a clinical case presenting an unusual periapical radiolucent lesion, its approach and treatment, and as an element of differential diagnosis in periapical pathology. Foreign body granuloma (FBG) is a tissue reaction that is triggered by the deposit of a foreign material affecting the skin and internal organs that the immune system tries to delimit and, if possible, eliminate. FBG may constitute a complication of a surgical procedure or a new pathology for the patient, which precedes an iatrogenic event causing diagnostic difficulties. This study presented an unusual periapical radiolucent lesion in a male patient with a periapical radiolucent area found in panoramic radiography; the lesion was enucleated, histopathologically confirming an FBG, which was the result of a biomaterial used in surgery for nasal polyps and deviated septum performed years before. This case shows us a very unusual presentation of an FBG within the maxillary bone after surgery for nasal polyps and deviated septum. The appropriate use of the available imaging tools and histopathological study and interpretation is emphasized, to be able to carry out a successful long-term treatment with the lowest chances of recurrence. In addition, an interdisciplinary approach is very important, which leads us to the comprehensive treatment of the patient. The proper use of diagnostic and imaging methods that we currently have, as well as knowledge of differential diagnoses, is essential to successfully diagnose and treat injuries in the maxillofacial area.